Evaluation of agronomic performance and genotypic mapping using SNP markers of grain iron and zinc content among rice accessions in Eastern Democratic Republic of Congo - Bukomarhe, C.B. (2024)
Rice (Oryza sativa L.) is among the most important food crop in the Democratic Republic of Congo (DRC). The crop has historically been neglected by local researchers. However, recent urbanization and changes in dietary habits have elevated its significance. The identification of rice varieties with high yield and reasonable micronutrient contents, especially iron (Fe) and zinc (Zn), could be important in rice varieties for the DRC. This study aimed to (a) determine agronomic performance of a subset of 36 rice accessions to identify high yielding and stable genotypes for cultivation in eastern DRC and (b) associate SNP markers with Fe and Zn content in rice grains for application in marker assisted selection. For the molecular markers study, 85 diverse rice accessions from the DRC maintained at the Kalemie were analysed for variation in Fe, Zn and SNP markers. The data were analysed using rMVP package of R software for Genome Wide Association Study (GWAS) to identify genomic regions linked to grain Fe and Zn content. Candidate genes associated with Fe and Zn content were identified and annotated from the Oryza sativa reference genome version 7.0 of the MSU-Rice Genome Annotation Project (RGAP) database. In the evaluated rice grains, Fe content ranged from 0.95 to 8.68 mg/100g (dry weight basis), while Zn content ranged from 0.87 to 3.8 mg/100g. Two significant SNPs were identified, with one on chromosome 11 associated with Fe and another on chromosome 4 associated with Zn. Candidate genes involved in transcription regulation and transporter activities related to Fe and Zn homeostasis, including the bZIP family genes and MYB family genes were pinpointed. For the agronomic trial, 36 rice accessions were evaluated in a 6x6 triple lattice design with three replications in Bwegera and Sange sites, in Eastern DRC. Data on various agronomic traits such as Day to Flowering (DTF), Plant Height (PH), Effective number of Tiller (ET), Panicle Length (PL), Grain per Panicle (GP), Thousand Grain weigh (TGW), Grain Length (GL), Grain Width (GW), Ratio Grain Length and Grain Weight (RGLGW), Grain Yield (GY) were recorded during growth and analysed using R software. Across locations, no significant differences were recorded in various agronomic variables, except for 1000-grain weight (TGW). Within locations, significant differences were observed for the evaluated variables except for panicle length, grain length, grain width, and the ratio of grain length to grain weight. Based on grain yield, accessions IR990-48-B-B-12, IR841, IR88638 and MR254 were the best across and within individual sites making them favorable recommendations for farmers. The identified markers and candidate genes can be utilized in Marker Assisted Selection (MSA) in rice breeding programs, aiming to enhance Fe and Zn content. The study is offering opportunities